PENERAPAN PSAK NO. 45 REVISI TAHUN 2015 PADA YAYASAN MADRASAH IBTIDAIYAH BAITUL MAKMUR KOTA KOTAMOBAGU - Sugeha, Aldiansyah; Lambey, Linda (Universitas Sam Ratulangi, 2017)
Along with the times, now a non-profit organization has been growing rapidly, for example a foundation engaged in educational, religious, health and others. Kotamobagu State Islamic Elementary School is an example of a foundation that is engaged in the field of education are categorized into non-profit organizations because it has the resources coming from student fees and parental contributions. As with any profit organizations, non-profit organizations also require knowledge of accounting to record expenses and revenues. In order to provide some form of responsibility and accountability to the community, the foundation is also required to prepare financial statements in accordance with the rules or standards that already exist. The purpose of this study was to determine the Financial Statements of Government Elementary School Baitul Makmur when applying PSAK No. 45. The method used is descriptive qualitative. Result shows that Government Elementary School have made a financial statement is still as simple as cash receipt book, cash expenditure book, the book recapitulation and did not make statements as set forth in PSAK No. 45.Keywords : PSAK, Nonprofit, Financial Statement